Pembelajaran Penemuan Terbimbing terhadap Kemampuan Generalisasi Matematis Siswa Sekolah Menengah Pertama - Yatha Yuni; Lesna Fisa (Journal of Instructional Mathematics, 2020)
The purpose of the research for to know the difference mathematical generalization ability of student are taught by use guided discovery learning and expository. The research was held at SMPN 21 Bekasi in second semester academic year 2016-2017. The sample is class VII.2 and VII.5 (76 students). This research used quasi-experimental with statistic group comparison or post-test-only with nonequivalent groups design. Instrument be used is an essay test to measure mathematical reflective thinking ability. Before tested instrument analyzed by correlation product moment to test the validity, reliability by formula alpha cronbach and an index of the lurch. The data is analyzed firstly be done test regulation is test normality with Lilliefors and also test homogeneity by using Fisher. The result of normality test of class experiment and control can be conclude that both of the sample are from normal distribution. While the result of homogeneity test can be conclude the population of both have a homogeneity variance. The result of research were obtained t result is 5,29 with significance ? is 0,05. The result of research showed a difference mathematical generalization ability of student through guided discovery learning and expository.